2015
DOI: 10.1017/s1368980015002530
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of the public on reducing population salt intake in Ireland

Abstract: Objective: As countries struggle to meet the set targets for population salt intake, there have been calls for more regulated approaches to reducing dietary salt intake. However, little is known about how the public perceives various salt reduction policies; an important line of investigation given that the implementation and success of these policies often depend on public sentiment. We investigated the attitudes and beliefs of consumers towards salt reduction and their support for thirteen different governme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…The survey included twenty-nine questions exploring knowledge on salt and salt reduction, consumer beliefs and behavioural intentions related to salt reduction, and consumer perspectives on strategies to reduce the population's salt intake. Survey design was informed by previous literature (25,26) , pilot studies, and consultations with public health practitioners and experts. Declarative salt knowledgefactual knowledge regarding intake of salt in the dietwas assessed using questions from previous literature, adapted to be culturally suitable (25,26) .…”
Section: Research Instrumentmentioning
confidence: 99%
See 1 more Smart Citation
“…The survey included twenty-nine questions exploring knowledge on salt and salt reduction, consumer beliefs and behavioural intentions related to salt reduction, and consumer perspectives on strategies to reduce the population's salt intake. Survey design was informed by previous literature (25,26) , pilot studies, and consultations with public health practitioners and experts. Declarative salt knowledgefactual knowledge regarding intake of salt in the dietwas assessed using questions from previous literature, adapted to be culturally suitable (25,26) .…”
Section: Research Instrumentmentioning
confidence: 99%
“…Survey design was informed by previous literature (25,26) , pilot studies, and consultations with public health practitioners and experts. Declarative salt knowledgefactual knowledge regarding intake of salt in the dietwas assessed using questions from previous literature, adapted to be culturally suitable (25,26) . Six questions assessed participants' understanding of dietary sources of salt intake, the maximum recommended daily salt intake (entered in grams per day or 'don't know') and the relationship between salt and health (see Table 2 for full wording of the questions).…”
Section: Research Instrumentmentioning
confidence: 99%
“…Reaching global salt reduction targets will require a multi-actor approach comprising of government, public health agencies, the food manufacturing industry, the restaurant and catering industry, scientists, health care professionals, and consumers working together [ 13 ]. Future research is needed to better understand the different viewpoints which drive the reformulation agenda and more broadly, the process through which salt reduction policies and strategies are developed [ 45 , 46 ]. In so doing, this will help to build a better understanding of the extent to which current strategies are being developed to meet the needs of consumers and whether more can be done to ensure that the voice of the consumer is being accounted for during the policy-making process.…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…Of these, 15 studies evaluated the effects of salt taxes, either through modeling ( n = 8) ( 31 38 ), real-world evaluation of impact ( n = 4) ( 39 – 42 ), experimental study ( n = 2) ( 43 , 44 ), or review of cost-effectiveness and cost-utility ( n = 1) ( 45 ). Two studies reported on consumer attitudes and stakeholder perceptions toward taxation of high-salt foods ( 42 , 46 ). Lastly, 6 studies provided information relevant to implementation of salt taxes in 5 countries ( 15 , 39 – 42 , 47 ), including the 4 real-world evaluation studies.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies reported on consumer attitudes toward salt taxation. In Ireland ( 46 ), salt tax was the least popular of proposed salt reduction initiatives, though 42% of those surveyed were in favor. Support for salt taxation was highest amongst those who saw food manufacturers as responsible for reducing salt consumption, suggesting knowledge of the food production process could be key to winning public support.…”
Section: Resultsmentioning
confidence: 99%